Essential Oil from Bark of Aniba parviflora (Meisn.) Mez (Lauraceae) Reduces HepG2 Cell Proliferation and Inhibits Tumor Development in a Xenograft Model. Issue 3 (15th February 2021) - de Oliveira, Felipe P.; da C. Rodrigues, Ana Carolina B.; de Lima, Emilly J. S. P.; Silva, Valdenizia R.; de S. Santos, Luciano; da Anunciação, Talita A.; Nogueira, Mateus L.; Soares, Milena B. P.; Dias, Rosane B.; Gurgel Rocha, Clarissa A.; Duvoisin Junior, Sérgio; Albuquerque, Patrícia M.; et al.
Abstract: Aniba parviflora (Meisn .) Mez (Lauraceae) is an aromatic plant of the Amazon rainforest, which has a tremendous commercial value in the perfumery industry; it is popularly used as flavoring sachets and aromatic baths. In Brazilian folk medicine, A. parviflora is used to treat victims of snakebites. Herein, we analyzed the chemical composition of A. parviflora bark essential oil (EO) and its effect on the growth of human hepatocellular carcinoma HepG2 cells in vitro and in vivo . EO was obtained by hydrodistillation and characterized by GC‐MS and GC‐FID. The main constituents of EO were linalool (16.3±3.15), α ‐humulene (14.5±2.41 %), δ ‐cadinene (10.2±1.09 %), α ‐copaene (9.51±1.12 %) and germacrene B (7.58±2.15 %). Initially, EO's cytotoxic effect was evaluated against five cancer cell lines (HepG2, MCF‐7, HCT116, HL‐60 and B16‐F10) and one non‐cancerous one (MRC‐5), using the Alamar blue method after 72 h of treatment. The calculated IC 50 values were 9.05, 22.04, >50, 15.36, 17.57, and 30.46 μg/mL, respectively. The best selectivity was for HepG2 cells with a selective index of 3.4. DNA Fragmentation and cell cycle distribution were quantified in HepG2 cells by flow cytometry after a treatment period of 24 and 48 h. The effect of EO on tumor development in vivo was evaluated in a xenograft model using C.B‐17 SCID mice engrafted with HepG2 cells. In vivo tumor growth inhibition of HepG2 xenograft at the doses of 40 and 80 mg/kg were 12.1 and 62.4 %, respectively. Abstract :